Understanding total quality management in context: qualitative research on managers’ awareness of TQM aspects in the Greek service industry - Alexandros Psychogios; Constantinos Priporas (2007)
This study addresses managers’ awareness and familiarity with Total Quality Management (TQM). Eighteen (18) semi-structured, in-depth interviews were conducted with managers working in a variety of service organizations in Greece. The major argument of the study is that although the acronym TQM and some of its concepts and practices are known by a range of public and private sector managers, actual awareness of its “soft” side is often superficial, and managers have a relatively poor understanding of it. TQM is neither resisted nor directly absorbed by them, but they tend to see it from the technical point of view, being aware only of the importance of its “hard” aspects.